EFFECTIVENESS OF APPLYING THE 5E MODEL IN TEACHING NATURAL SCIENCES IN PRIMARY EDUCATION - Kurbanov Sanjar Rajabboyevich (Bright Mind Publishing, 2025)
This article highlights the scientific and theoretical foundations and practical advantages of organizing natural science lessons in primary grades based on the 5E model (attraction, research, explanation, expansion, and assessment). The model serves as an effective tool for the development of students' scientific thinking, ensuring their active participation.
Keywords: 5E model, primary education, science, interactive method, student activity.